Studi Praktikum Anatomi dan Fisiologi Manusia: Analisis Golongan Darah Menggunakan Metode Aglutinasi - Azzahra, Zahwa Fatimah (Maliki Interdisciplinary Journal, 2025)
Blood is a vital component in the body that functions in transporting oxygen, nutrients, and metabolic waste products, as well as in the body's immune system. Blood typing is important to prevent immune reactions during medical procedures such as blood transfusions. This study aims to identify the ABO blood type system in students using the slide method, understand the basic principles of antigen-antibody agglutination, and relate them to the physiology of the immune system and circulation. The test was conducted on three subjects using A, B, and AB antisera. The results showed one subject with blood type A, one with B, and one with O. Agglutination reactions occurred according to the presence of antigens on the surface of red blood cells. These observations indicate a strong correlation between blood type, immune reactions, and the stability of the circulatory system. Blood type incompatibility can trigger immune reactions such as agglutination and hemolysis, which carry the risk of causing serious complications. Thus, blood typing through the simple agglutination method is not only useful as a practical exercise but also as a means of understanding the physiological aspects of the human immune system and blood circulation.